Turkish Constitutional development and assembly debates on the Constitutions of 1924 and 1961. Dr. Suna KiLi - Mantilla Pineda, Benigno (Estudios de Derecho, 1972)
Turkish Constitutional development and assembly debates on the Constitutions of 1924 and 1961. Dr. Suna KiLi (Member of the Faculty of the Bosphorus University)